2021
DOI: 10.17323/2500-2597.2021.1.39.54
|View full text |Cite
|
Sign up to set email alerts
|

Perception of New Technologies: Constructing an Innovation Openness Index

Abstract: Rapid technological progress is one of the basic processes in the modern world. It is an integral part both in the field of labor and employment and in leisure and recreation. The request for an accelerated implementation of digital technologies in the economy and social sphere, which is inherent in one of the national development goals of the Russian Federation, makes this topic more important. In the presence of technological challenges, people have to adapt to constantly emerging innovations. Meanwhile the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Some of the constraints to the utilisation of digital technologies by smallholder farmers in South Africa has been due to the perceptions towards digital technologies. However, openness to digital technologies is determined by the combination of perception and socio-economic characteristics [7]. Caffaro et al [8] identified that perceptions towards digital technologies relate to usefulness, increased productivity, cost reduction, efficiency, and workload reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the constraints to the utilisation of digital technologies by smallholder farmers in South Africa has been due to the perceptions towards digital technologies. However, openness to digital technologies is determined by the combination of perception and socio-economic characteristics [7]. Caffaro et al [8] identified that perceptions towards digital technologies relate to usefulness, increased productivity, cost reduction, efficiency, and workload reduction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, among Russians, those with lower levels of education are more frequently afraid of secret "chipping" through vaccination against COVID-19. Additionally, people with higher education are more open to innovation [Pishnyak, Khalina, 2021], so they might perceive this technology differently than those without higher education.…”
Section: Methodsmentioning
confidence: 99%
“…The authors tried to analyze these issues in relation to the entrepreneurial ecosystem, but similar gaps appear in the innovation ecosystem, too. The necessity of analyzing the perception of innovations by a population is further confirmed by Pishniak and Khalina [19]. These authors managed to draw up a "portrait" of domestic representatives of society, ready to try and use innovative developments, who are "young, educated, successful people without a fear of new technologies".…”
Section: Literature Reviewmentioning
confidence: 99%